Coronary Artery Involvement in Kawasaki Disease-Echocardiographic Evaluation of Cases in a Tertiary Care Hospital (Cardiovascular Journal, 2023)
Background: Kawasaki disease (KD) is the leading cause of childhood acquired heart disease. Cardiovascular manifestations can be prominent in the acute phase of the illness. Echocardiography is useful in recognizing these cardiac manifestations. We carried out a retrospective study by analyzing the data of Kawasaki disease patients in a tertiary care hospital.Methods: The prevalence of coronary artery dilatation and clinical outcome were documented. Clinical, laboratory, and echocardiographic findings were obtained at baseline and 1 week, 6 weeks after initial therapy with intravenous immunoglobulin in addition to high doses of Aspirin which reduces the risk of coronary artery aneurysm.Results: One hundred and forty-nine patients with mean age 3± 2 years old, 60% males with Kawasaki disease were included. One hundred and thirty-two patients had coronary involvement (left main coronary artery 36.37 %, left anterior descending artery 28.03%, right main coronary artery 24.25%, circumflex branch in 11.37%). Administration of intravenous immunoglobulin (IVIG) and aspirin has greatly reduced the incidence of coronary lesions in affected children. The initial cardiac findings developed over first few weeks of illness resolved in most of the cases in the subsequent echocardiogram studies after IVIG. The mean duration to normalization of abnormal echocardiography findings is 6±3 months.Conclusion: Coronary artery involvement is seen in most of children with Kawasaki disease. Intravenous gamma globulin and aspirin has been reported to reduce the likelihood of development of giant coronary artery aneurysms and appears to have a direct beneficial effect on abnormalities in cardiac function associated with the acute phase of Kawasaki disease.Cardiovasc j 2023; 15(2): 144-150